MENEKAN ANGKA PERKAWINAN ANAK: Sinergi Peranan Pemerintah dan Ormas Keagamaan - Khafsoh, Nur Afni; Riani, Nur; Adha Anggraini; Muhammad Ghufron; Anisha Rizki Utami; Nur Hanifah Ahmad (Mukaddimah: Jurnal Studi Islam, 2024)
The rate of child marriage in the Special Region of Yogyakarta is quite high with 715 cases in 2021. Meanwhile, Yogyakarta City had the highest rate of child marriage with 228 cases. The negative impact of child marriage is not only in terms of health but also mental (psychological) and economic. This research looks at the role of each institution and specifically highlights women's religious institutions in responding to the phenomenon of child marriage. This research uses a qualitative approach with structuralist functional theory as an analytical tool. Primary data sources were obtained through in-depth interviews and secondary data through notes, news, and other documentation. Data analysis techniques through reduction, presentation, analysis, and conclusion. The results are the role in overcoming child marriage in Yogyakarta is carried out by the Women's Empowerment and Child Protection and Family Planning Service (DP3AP2AKB) KUA, Religious Courts, Puspaga, UPT PPA, PKK who synergize in carrying out prevention through socialization programs, administratively carrying out records and the process of providing dispensations, and psychological assistance to both children and parents. Women's religious organizations are carrying out massive outreach programs in the community. Fatayat and Aisyiyah have unique programs according to the characteristics of their respective organizations.